The permeability of active subduction plate boundary faults. Issue 1 (1st October 2014) - Saffer, D. M.
Abstract: At subduction zones, continuous influx of fluids drives a dynamic system in which fault slip, fluid flow, and advective transport are tightly coupled. Field and numerical modeling studies have provided insight into the nature and rates of flow in these systems and illustrate that active subduction faults, including the master décollement and splay faults cutting the upper plate, are important conduits. Observations of in situ fracture dilation, modeling studies, and direct measurements documenting strong pressure dependence of fault permeability collectively suggest that permeability varies in time, perhaps due to pore pressure cycling. However, mechanical and fluid budget considerations dictate that increased fault permeability cannot be sustained, nor can it be present across the entire fault surface at a given time. The emerging conceptual model is that permeable patches or channels occupy only a fraction of the fault surface and shift transiently. Fault zone permeabilities obtained by several approaches are consistent between margins, with time‐averaged values of approximately 10 −15 to 10 −14  m 2, several orders of magnitude higher than for the sediment matrix. Higher, transiently increased values of approximately 10 −13 to 10 −11  m 2 are required to explain geochemical and thermal signals and observed focused flow rates. Although faults accommodate significant fluid fluxes from dewatering of the surrounding sediment, they have little effect on pore pressures within the wall rock, where drainage is limited by low matrix permeability. However, fault permeability is a key control on the transport and preservation of localized geochemical and thermal anomalies from depths where temperatures are higher and low‐temperature metamorphic reactions are underway. Despite significant recent progress, several key aspects of hydrologic behavior in these active faults remain incompletely understood, including the nature and timescale of transience, the causes of permeability enhancement and its relationship to fault slip and pore pressure fluctuations, and the depths and distances from which deeply sourced fluids are captured, mixed, and transported up‐dip. Abstract : Subduction zone faults are key conduits for fluid flow and advection of heat and solutes. Drilling, numerical modeling, and laboratory studies all suggest that their permeability also varies through time, likely due to pore pressure cycling and dilation of fracture networks. Detailed studies of several active subduction zones illustrate that both time‐averaged and transiently elevated fault permeabilities are remarkably consistent between margins, ranging from approximately 10 −15 to 10 −14  m 2 and approximately 10 −11 to 10 −13  m 2, respectively, and are up to six orders of magnitude higher than that of the surrounding sediment matrix.